The Effect of Exposure Qari and Qariah Recitation During Pregnancy to the Number of Astrocyte Glia Cells in the Cerebrum Newborn Rattus Norvegicus (Indian Journal of Forensic Medicine & Toxicology, 2021)
The quality of human resources should be prepared since in early stage. Pregnancy is one of a significantperiod which can take advantage to by providing proper nutrition and adequate stimulation. For instance,sound and music, the most harmonious combination and easily accepted by the fetus(1). Experimentalanalytic type with post-test only control group design was employed on 30 pregnant Rattus norvegicus whichwere divided randomly into 3 groups, namely the control group, qari group, and qariah group. Each of thegroups had stimulation starting 6th to 17th days of pregnancy for 60 minutes. At 18 days of pregnancy, themother of Rattus Norvegicus was sacrificed and bring forth with Sectio Caesarea (SC). As a result, thenumber of astrocyte glia cells in the cerebrum was higher in the qaria recitation stimulation group (22.62 ±3.75), compared with the group that was listened to qari recitation stimulation group (19.84 ± 2.48), whilethe control group (16.54 ± 2.78). A significant difference found in the number of astrocyte glia cells inthe Cerebrum Rattus norvegiccus newborn that were listened to the qari and qariah recitation stimulationgroup and the control group. The highest number of Glia cells is obtained from the stimulation of qariahrecitation.